2009
DOI: 10.1007/s12272-009-1910-x
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase inhibitive activity-guided isolation of two new alkaloids from seeds of Peganum nigellastrum Bunge by an in vitro TLC- bioautographic assay

Abstract: Acetylcholinesterase inhibitors (AChEIs) currently form the basis of the newest drugs available for the treatment of Alzheimer's disease. For the aim of screening effective AChEIs, the methanol extracts of the seeds of genus Peganum were found to show significant inhibitory activity of acetylcholinesterase enzyme (AChE) using an in vitro TLC-bioautographic assay. In further studies to seed of P. nigellastrum Bunge, activity-guided fractionation led to the isolation of two new alkaloids nigellastrine I (9) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 17 publications
2
55
0
1
Order By: Relevance
“…Former research of our group revealed that harmaline and harmine, accounting for more than 70% in composition, were the main alkaloids in extracts. Both of them exhibited strong AChE inhibitive activity remarkably superior to other alkaloids in P. harmala [20]. More attention, however, should be paid to the other alkaloids which would be favorable or unfavorable to the efficacy and safety of the products.…”
Section: Quantitative Analysis Of Vasicine Harmalol and Harmolmentioning
confidence: 93%
See 2 more Smart Citations
“…Former research of our group revealed that harmaline and harmine, accounting for more than 70% in composition, were the main alkaloids in extracts. Both of them exhibited strong AChE inhibitive activity remarkably superior to other alkaloids in P. harmala [20]. More attention, however, should be paid to the other alkaloids which would be favorable or unfavorable to the efficacy and safety of the products.…”
Section: Quantitative Analysis Of Vasicine Harmalol and Harmolmentioning
confidence: 93%
“…Harmine and harmaline showed special affinity to the central nervous system (CNS) and exhibited extensive bioactivities such as multi-enzymes inhibitions including monoamine oxidaze type-A [7,8], cyclin-dependent kinases [9], N-acetyltransferase [10] and Na-K ATPase [11], cytotoxicity and antitumour activities [12,13], anti-bacterial activity [14], antiplasmodial activity [15], antileishmanial activity [16], immunomodulator properties [17], temperature-lowering effect [18], cardiovascular actions [19] and so on. Recent research reported that the alkaloids showed potential inhibitory effects on the acetylcholinesterase (AChE) activity using an in vitro thin-layer chromatography (TLC)-bioautographic assay, and ten alkaloids isolated were evaluated based on their inhibitory ability [20]. Considering its potential effect on the treatment of Alzheimer's disease (AD), ten batches of total alkaloids extracts from seeds of P. harmala were prepared for pharmacologic research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, they have also been proved to cause oxidative modification of low-density lipoprotein particles, which can reduce severe atherosclerosis [10]. Harmaline [ Figure 1], a di-hydro beta carboline alkaloid, is such a plant alkaloid isolated from the seeds and roots of Peganum harmala (Syrian rue) [11] and have wide range of biological actions including anti-leishmanial [12], insecticidal [13], acetylcholinesterase inhibition [14], central monoamine oxidase inhibition [15], and in vitro human topoisomerase I inhibition effects [16] and in vitro cytotoxic effects [17]. Another beta carboline alkaloid harmine and its derivatives were also proved to be cytotoxic against different cancer cell lines [18].…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, there is a clear trend towards the use of the TLC bioautography technique as a method for screening active compounds against microorganisms rather than a method for the detection of enzyme activities or inhibitors. The use of TLC (bio)autography was reported for the screening of inhibitors of acetylcholinesterase [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] , butyrylcholinesterase 12,16,22,23,27 , dipeptidyl peptidase IV 28 , glucose-6-phosphate dehydrogenase 29 , a-and b-glucosidases [30][31][32][33][34] , lipase [35][36][37] , monoamine oxidases A and B 38,39 , DNA topoisomerase I 40 , tyrosinase [41][42][43] and xanthine oxidase 44 . To date, the use of the TLC-based autographic method for the detection of PGI inhibition has only been developed for a biocatalyst isolated from the reference E. coli strain ATCC (American Type Culture Collection) 25922 45 .…”
Section: Introductionmentioning
confidence: 99%